THE IMPORTANCE OF USING THE CASE STUDY METHOD IN BIOLOGY CLASSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the structure, implementation stages and methods of using the method of biology lessons in problem-based learning technologies in secondary schools.